Evidence of Scaling in Chinese Income Distribution - Yan, Xu; Liang-Peng, Guo; Ning, Ding; You-Gui, Wang (Chinese physics letters, 2010)
With income data from Chinese household income projects in 1998--2002, we study the functional form of Chinese income distribution. The fitting results suggest a log-normal distribution plus a power-law tail. This distributional form has changed a lot from its appearance in the early stage of China's reform and turns out to be consistent with that of some complete market economies. The uncertainty and diversity of income growth rate aroused by marketing reform are the main causes of current Chinese income distribution.